2016
DOI: 10.1073/pnas.1603106113
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for universal HLA-A*0201–restricted CD8 + T-cell immunity against influenza viruses

Abstract: Memory CD8+ T lymphocytes (CTLs) specific for antigenic peptides derived from internal viral proteins confer broad protection against distinct strains of influenza A virus (IAV). However, immune efficacy can be undermined by the emergence of escape mutants. To determine how T-cell receptor (TCR) composition relates to IAV epitope variability, we used ex vivo peptide-HLA tetramer enrichment and single-cell multiplex analysis to compare TCRs targeted to the largely conserved HLA-A*0201-M1 58 and the hypervariabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
179
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(205 citation statements)
references
References 41 publications
20
179
4
Order By: Relevance
“…S1a). From the analysed cells, we identified new as well as previously described22232930 Flu MP 58-66 -specific T cell receptor chains (see Supplementary Table S1). We noted inter-individual sharing of TCR α-chains among the analysed Flu-specific cells (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S1a). From the analysed cells, we identified new as well as previously described22232930 Flu MP 58-66 -specific T cell receptor chains (see Supplementary Table S1). We noted inter-individual sharing of TCR α-chains among the analysed Flu-specific cells (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Assessment of cell division revealed that all memory CD8 + T cell subsets were capable of undergoing in vitro expansion with, on average, 60%-70% of cells within each subset undergoing at least 1 division after 10 days of culture ( Figure 3, B and C). A comparison of the effector function of the divided cells following a brief restimulation revealed that, across all the subsets, 70%-85% of the divided cells could generate IFN-γ and 80%-90% could synthesize TNF-α, reflecting that the progeny of each of the memory CD8 + T cells subsets had supe- (5,16). As predicted, CD8 + T cells directed at distinct epitopes displayed different biases in TCR-β variable (TRBV) and TCR-α variable (TRAV) usage as well as different lengths of complementarity-determining region 3α (CDR3α) and CDR3β loops ( Figure 5).…”
Section: Enrichment Of Influenza-specific Cd8mentioning
confidence: 99%
“…EBV-and herpes simplex virus-specific clones have been shown to also react to allogeneic HLA in humans, particularly within the CD8 compartment (21,(61)(62)(63)(64)(65); it has even been suggested that nearly half of the TCRs specific to a given virus may also have alloreactivity (66). Furthermore, these viral peptide-specific TCRs may have "public" sequences shared between individuals with the same presenting HLA allele (67)(68)(69)(70). Notably, cytokine production and other measures of T cell function are not always identical in response to viral antigen and cross-reactive HLA alloantigens (21), perhaps because of differing TCR affinities for different ligands.…”
Section: Methods For Measuring the Alloresponsementioning
confidence: 99%